2014
DOI: 10.3171/2014.4.peds13547
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Mycoplasma hominis infections after neurosurgical intervention

Abstract: Object Mycoplasma hominis is a rare cause of infection after neurosurgical procedures. The Mycoplasma genus contains the smallest bacteria discovered to date. Mycoplasma are atypical bacteria that lack a cell wall, a feature that complicates both diagnosis and treatment. The Gram stain and some types of culture media fail to identify these organisms, and typical broad-spectrum antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 24 publications
(32 reference statements)
0
21
0
1
Order By: Relevance
“…By carefully reading all the papers, we found that there were only 19 reported non-neonatal-associated cases of CNS infection caused by M. hominis ; none was reported from China (Table 1 ). Of these 20 cases, brain abscess was the most common CNS infections ( n = 13) [ 3 , 10 , 14 – 23 ], followed by meningitis ( n = 4) [ 8 , 24 26 ], spinal cord abscess ( n = 1) [ 2 ], subdural empyema ( n = 1) [ 27 ], (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By carefully reading all the papers, we found that there were only 19 reported non-neonatal-associated cases of CNS infection caused by M. hominis ; none was reported from China (Table 1 ). Of these 20 cases, brain abscess was the most common CNS infections ( n = 13) [ 3 , 10 , 14 – 23 ], followed by meningitis ( n = 4) [ 8 , 24 26 ], spinal cord abscess ( n = 1) [ 2 ], subdural empyema ( n = 1) [ 27 ], (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma hominis , initially described as pleuropneumonia-like organism, is a commensal of the human oral cavity, respiratory tract, and genitourinary tract [ 1 3 ]. However, its role in the pathogenesis of infections in adult patients, especially extragenital infections such as central nervous system (CNS) infection, post-operative wound infections, mediastinitis, and septic arthritis [ 2 , 4 7 ], has been difficult to determine. M. hominis , which does not possess a cell wall and hence is not identifiable by Gram staining of clinical specimens, is difficult to detect [ 3 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, CNS infections due to M. hominis are very rare and only 13 cases of brain abscesses have been reported to date. [1][2][3] We report herein the occurrence of an M. hominis brain abscess after a head trauma, which was rapidly identified by matrix-assisted laser desorption/ ionization time-of-flight mass spectrometry (MALDI-TOF MS; VITEK MS, bioMé rieux).…”
Section: Introductionmentioning
confidence: 99%
“…Effective antimicrobials do exist, but their continuous applications in cell culture is not recommended because of the toxicity to cells. Finally, mycoplasma is a atypical bacteria, causing difficulities in correct diagnosis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%